You want to use the rules of exponents.
1. (x^a) (x^b) = x^(a+b)
e.g. (x^2) (x^3) = x^5
Why: (x^2) (x^3) = (x x) (x x x) = (x x x x x) = x^5
2. (x^a) / (x^b) = x^(a-b)
e.g. (x^5) / (x^3) = (x^2)
Why: (x^5) / (x^3) = (x x x x x) / (x x x) = (x x) [(x x x) / (x x x)] = (x x) (1) = x^2
3. (x^a)^b = x^(ab)
e.g. (x^3)^2 = x^6
Why: (x^3)^2 = (x^3) (x^3) = x^6
------------------------------------------------------------------------------------------------
In your problem, group all the coefficients (real numbers), and like variables together on the top and bottom:
[(15) (2) (a^8) (b^6) (b^2)] / [(3) (a) (a^3) (b^3) (b^8)]
Then apply rule 1 followed by rule 2.
[30 a^8 b^8] / [3 a^4 b^11]
= (10 a^4) / (b^3) <-- here b^3 is left in the denominator because b^8 cancels on the top and bottom, leaving b^3 on the bottom, and none (i.e. b^0) on the top.
Comments